Climate Change Impacts on Future Rainfall in Padas River Basin, Sabah, Malaysia using Statistical Downscaling Method - Sazali Othman; Mohamed Rodzi, Muhammad Syukri; Lim, Foo Hoat; Rahmat, Siti Nazahiyah; Tukimat, Nurul Nadrah Aqilah; Othman, Wan Zunairah; Muhammad Hanafi (International Journal of Integrated Engineering, 2025)
The objective of this study was to assess the influence of climate change on the rainfall across the Padas River Basin, Sabah, Malaysia. Observed rainfall data (1985-2014) and downscaled climate model outputs (2025-2100) from four of the most suitable Global Climate Models (GCMs) (CMCC-CM2, IPSL-CM6A, MIROC6 and MRI-ESM2) were employed. The projected rainfall trend was analysed based on the 10th (P10), 50th (P50) and 90th (P90) percentiles to assess low, median, and high rainfall scenarios, allowing a more comprehensive understanding of uncertainty and risk in future rainfall patterns. The projection suggest an overal increase in rainfall for all months in the future, attributable to a lengthened wet season during the study period. Compared with the historical baseline, the highest monthly increase is projected in May (+60.3 mm), followed by Nov (+46.8 mm), while Feb shows the smallest increment (+5.5%). The projected increase in monthly rainfall between May and November may elevate future flood risks. Annual rainfall is expected to rise by approximately 5.4% (2025-2050) and 7.4% (2051-2100), with the highest intensity concentrated near coastal areas. Under SSP2–4.5 and SSP5-8.5, the mean annual rainfall is projected less than 3,625 mm and 4,030 mm, respectively. All four (4) models indicate a similar spatial rainfall pattern, with the northeastern part of the basin receiving more rainfall. In the long-term P90 scenario, coastal areas are projected to experience higher rainfall with cumulative rainfall less than 300,000 mm over the 76 years period. Meanwhile, the long-term P50 scenario shows results consistent with historical monthly data. These findings are essential for water management and long-term sustainability of water resources under changing climatic conditions.